Nanoflagellates (mixotrophs, heterotrophs and autotrophs) in the oligotrophic eastern Mediterranean - Urania Christaki; France Van Wambeke; John Dolan (PANGAEA, 1999)
The vertical distribution (0 to 100 m) and abundance of nanoflagellates were examined in the oligotrophic Aegean Sea (east Mediterranean) in early spring (south basin) and late summer (north and south basins) of 1997 in the framework of the MATER project (Mass Transfer and Ecosystem Response). Different trophic types of nanoflagellates (mixotrophic, heterotrophic, and phototrophic) were identified based on the possession of chloroplasts and the consumption of Fluorescently Labelled Minicells (FLM). Bacterial production (leucine method) was compared with bacterivory estimated from FLM consumption. We found that mixotrophic nanoflagellates played a small role as bacterivores relative to heterotrophic nanoflagellates and total bacterivory roughly balanced bacterial production. In early spring with cool (14.2°C) well-mixed water columns, flagellate concentrations were lowest, phototrophic flagellates were the dominant group and concentrations varied little with depth. Average concentrations of mixotrophs, heterotrophs and autotrophs were 0.07, 0.34, and 0.64 x 103 cells/ml, respectively. Bacterial production in the 0 to 100 m layer averaged about 0.74 μg C/l/d. Estimated nanoflagellate bacterivory from FLM ingestion accounted for 40% of bacterial production with mixotrophic nanoflagellates consuming 5% of bacterial production. In late summer, total nanoflagellate concentrations were higher. Average concentrations of mixotrophs, heterotrophs and autotrophs were 0.09, 1.14, and 0.66 x 103 cells/ml, respectively, in the southern basin and 0.09, 1.1, and 0.98 x 103 cells/ml, respectively, in the northern basin. In September, bacterial production for both basins roughly balanced estimated nanoflagellate consumption. Similar to the March estimates, mixotrophic nanoflagellates accounted for about 5% of nanoflagellate bacterivory. In a nutrient enrichment experiment in March, treatments including phosphorus resulted in increased bacterial production and reductions in identifiable mixotrophs.
Supplement to: Christaki, U et al. (1999): Nanoflagellates (mixotrophs, heterotrophs and autotrophs) in the oligotrophic eastern Mediterranean: standing stocks, bacterivory and relationships with bacterial production. Marine Ecology Progress Series, 181, 297-307, https://doi.org/10.3354/meps181297